CRISPR-Cas9 Based Genome Editing Reveals New Insights into MicroRNA Function and Regulation in Rice - Zhou, Jianping; Deng, Kejun; Cheng, Yan; Zhong, Zhaohui; Tian, Li; Tang, Xu; Tang, Aiting; Zheng, Xuelian; Zhang, Tao; Qi, Yiping; Zhang, Yong (Frontiers in Plant Science, 2017)
MicroRNAs (miRNAs) are small non-coding RNAs that play important roles in plant development and stress responses. Loss-of-function analysis of miRNA genes has been traditionally challenging due to lack of appropriate knockout tools. In this study, single miRNA genes (OsMIR408 and OsMIR528) and miRNA gene families (miR815a/b/c and miR820a/b/c) in rice were targeted by CRISPR-Cas9. We showed single strand conformation polymorphism (SSCP) is a more reliable method than restriction fragment length polymorphism (RFLP) for identifying CRISPR-Cas9 generated mutants. Frequencies of targeted mutagenesis among regenerated T0 lines ranged from 48% to 89% at all tested miRNA target sites. In the case of miRNA528, three independent guide RNAs (gRNAs) all generated biallelic mutations among confirmed mutant lines. When targeted by two gRNAs, miRNA genes were readily to be deleted at a frequency up to 60% in T0 rice lines. Thus, we demonstrate CRISPR-Cas9 is an effective tool for knocking out plant miRNAs. Single-base pair (bp) insertion/deletion mutations (indels) in mature miRNA regions can lead to the generation of functionally redundant miRNAs. Large deletions at either the mature miRNA or the complementary miRNA* were found to readily abolish miRNA function. Utilizing mutants of OsMIR408 and OsMIR528, we find that knocking out a single miRNA can result in expression profile changes of many other seemingly unrelated miRNAs. In a case study on OsMIR528, we reveal it is a positive regulator in salt stress. Our work not only provides empirical guidelines on targeting miRNAs with CRISPR-Cas9, but also brings new insights into miRNA function and complex cross-regulation in rice.